2023
DOI: 10.5933/jkapd.2023.50.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness and Cariogenic Microbial Adhesion after Polishing of Smart Chromatic Technology-based Composite Resin

Abstract: This study compared the surface roughness and microbial adhesion characteristics of Omnichroma, a novel composite resin developed using “smart chromatic technology”, with those of two other conventional composite resins with different filler compositions. A total of 144 specimens were fabricated using 3 types of composite resins: Omnichroma (nano-spherical), Filtek Z350XT (nanofill), and Tetric N-Ceram (nanohybrid) and, divided into 3 groups of 48. Finishing was performed using tungsten carbide burs. Specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…These findings are in line with studies conducted by Naser-Alavi et al 11 and Amaya-Pajares et al 12 , which demonstrated that nano hybrid composites show better polish ability than micro hybrid composites. However, it was found in another study by Kim et al 13 that nano hybrid composite had lower smoothness and polish ability to micro hybrid composite. Because nano hybrid composite has a lower surface roughness and better polish ability than micro hybrid composite, this study's findings are encouraging and consistent with many earlier investigations.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are in line with studies conducted by Naser-Alavi et al 11 and Amaya-Pajares et al 12 , which demonstrated that nano hybrid composites show better polish ability than micro hybrid composites. However, it was found in another study by Kim et al 13 that nano hybrid composite had lower smoothness and polish ability to micro hybrid composite. Because nano hybrid composite has a lower surface roughness and better polish ability than micro hybrid composite, this study's findings are encouraging and consistent with many earlier investigations.…”
Section: Discussionmentioning
confidence: 88%